Calcium Silicate Application Enhances Oxidative Defense and Improves the Physiological and Growth Responses of Shallot (Allium cepa L. Aggregatum Group) Under Salinity Stress - Sidiq Permana Putra; Sukirno Sukirno; Laurentius Hartanto Nugroho; Diah Rachmawati (Universitas Sebelas Maret, 2025)
Indonesia’s shallot production still falls short of domestic demand, necessitating imports. Expanding cultivation into marginal coastal areas such as Yogyakarta is promising but constrained by soil salinity. Silicon can help by enhancing plant resistance to such abiotic stress. This study evaluated the physiological and biochemical responses of shallot plants (Allium cepa L. Aggregatum group) to the application of calcium silicate (CaSiO3) under saline conditions. The experiment employed a completely randomized design with 2 factors: CaSiO3 (0, 2, and 4 mM) and salinity (0, 2, 4, and 8 dS m⁻¹), each with 5 replications. Physiological parameters, antioxidant activity, and yield traits were analyzed using analysis of variance (ANOVA) followed by Duncan multiple range test (DMRT) at p ≤ 0.05. CaSiO3 significantly alleviated salt stress by enhancing superoxide dismutase (SOD) activity and membrane stability, improving photosynthetic efficiency, promoting growth, and yield components. Under high salinity, 4 mM CaSiO3 reduced proline and H₂O₂ accumulation compared with untreated plants. These findings indicate that applying 4 mM CaSiO3 can enhance shallot productivity and resilience in saline coastal soils, supporting sustainable shallot self-sufficiency in Indonesia.